Analysis of the transition effect of monetary policy on credit and deposit rates in the covid-19 period: The case of Turkey - ALKAN, UFUK (My University, 2022)
The aim of this study; The aim of this study is to examine how the short-term interest rates controlled by the CBRT between the years 2019-2021 affect the loan and deposit rates and the pass-through effect of interest rates in Turkey. In the study, the relationship between the interest rates under the control of the CBRT and short-term interest rates and which interest rate is more determinant were tried to be determined. Therefore, the question of which central bank interest is related to which loan interest or deposit interest is important. In our study, in which short-term relationships were examined using monthly data between the years 2019-2021, the GMM technique was preferred in order to measure dynamic relationships. It is possible to collect the results of the study under three main headings. Interest rate pass-through was analyzed over actual interest rates and it was determined that all interest rate variables were significant. However, the fact that actual interest, not legal interest, determines deposit and loan interests has been confirmed in our study. In addition, it has been shown that not a single interest, but different rates are valid for different types of loans and deposits. Finally, while AOFM is the most effective in commercial loans and housing loans, the interest type with the highest market pass-through from consumer loans, consumer loans and deposit rates was found to be TL reference interest. BIST Repo rate is most effective in vehicle loans
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Monetary Policy; Transition Effect; Interest Rates; Generalized Moments Method (GMM)